(untitled) (Research, Society and Development, 2022)
This work aims to carry out an integrative review of the literature, in order to gather studies that show the relationship between the presence of genetic polymorphisms associated with leptin and the development of obesity. This is an integrative literature review, based on the following steps: elaboration of the guiding question, literature search or sampling, data collection, critical analysis of the included studies, discussion of the results and presentation of the integrative review (Souza, Silva & oak, 2010). The guiding question was: Can leptin-associated genetic variants exert effects on the development of obesity? Initially, the strategy for the search for studies consisted of a combination of controlled descriptors (leptin, disorders, metabolism, polymorphisms and obesity) indexed in the Health Sciences Descriptors (DeCS/MeSH). In the first screening, based on the inclusion and exclusion criteria, 14073 studies were eliminated. After eligibility/critical evaluation of the full texts of 360 records, 5 met the inclusion criteria and proceeded to the data extraction, exhaustive reading and knowledge synthesis phase. The results presented and discussed indicate a relationship between the presence of genetic variants and changes in the process of leptin synthesis, as well as changes in the process of binding the hormone to its receptors, impacting metabolic processes that favor obesogenesis.